Republic of Sierra Leone Priorities for Sustainable Growth and Poverty Reduction : Systematic Country Diagnostic - World Bank Group (World Bank, Washington, DC, 2018)
The objective of this Systematic Country Diagnostic (SCD) is to describe the current development challenges facing Sierra Leone and offer a set of priority areas of intervention to further the twin goals of reducing extreme poverty and boosting shared prosperity. The SCD is designed to be an evidence driven exercise that draws together diverse findings into a comprehensive country diagnostic. The SCD argues that, without taking into account the two main foundational constraints governance and fiscal space, it is unlikely that the proposed technical solutions will make a substantial impact on the twin goals. Many of the technical solutions that are in this document have been tried in multiple variations over the last 60 years by government, donor partners, and other stakeholders, but the results have been meager. Despite favorable geography and abundant resources, and after hundreds of millions of dollars in soft loans and grants, smart consultants, sound technical approaches, Sierra Leone continues to have development outcomes that rate among the worst in the world. This SCD argues that unless governance constraints are understood and mitigated this situation is unlikely to change very much. It further takes into account severe fiscal constraints in proposing ways to alleviate this while also avoiding reforms that require substantial financial outlays. If the two foundational issues are appropriately addressed, the priority technical interventions proposed here have the potential to unlock growth, reduce poverty, and improve the lives of the Sierra Leonean population.